Electric vehicles : technology brief (International Renewable Energy Agency, 2017)
The global stock of electric vehicles (EVs) reached 1 million in 2015 and exceeded 2 million by the end of 2016. Yet faster growth is needed for EVs to fulfil their role in the global energy transition, both through lowering vehicle emissions and boosting renewable energy use. This brief outlines the technological and policy advances still needed for EVs to help drive the transition to a sustainable global energy future. Increasing reliance on EV batteries and charging stations would support higher shares of solar and wind power, the key variable renewable energy (VRE) sources expected to be prominent in future power grids. Transport accounts for about 30% of global energy use. EVs, therefore, form a crucial part of REmap - the global roadmap from the International Renewable Energy Agency (IRENA) to double renewables in the energy mix by 2030. Global growth to 160 million EVs could support VRE-based power generation on a large scale, the analysis finds.